Qualitative and quantitative detectability of hypertrophic olivary degeneration in T2, FLAIR, PD, and DTI: A prospective MRI study - Steidl, Eike; Rauch, Maximilian; Hattingen, Elke; Breuer, Stella; Schüre, Jan Rüdiger; Grapengeter, Marike; Shrestha, Manoj; Foerch, Christian; Schaller-Paule, Martin A. (Frontiers in Neurology, 2022)
Purpose: Hypertrophic olivary degeneration (HOD) is a pathology of the inferior olivary nucleus (ION) that occurs after injuries to the Guillain-Mollaret triangle (GMT). Lacking a diagnostic gold standard, diagnosis is usually based on T2 or FLAIR imaging and expert rating. To facilitate precise HOD diagnosis in future studies, we assessed the reliability of this rater-based approach and explored alternative, quantitative analysis. Methods: Patients who had suffered strokes in the GMT and a matched control group prospectively underwent an MRI examination including T2, FLAIR and proton density (PD). Diffusion tensor imaging (DTI) was additionally performed in the patient group. The presence of HOD was assessed on FLAIR, T2 and PD separately by 3 blinded reviewers. Employing an easily reproducible segmentation approach, relative differences in intensity, fractional anisotropy (FA) and mean diffusivity (MD) between both IONs were calculated. Results: Fifteen patients were included. The interrater reliability was best for FLAIR, followed by T2 and PD (Fleiss κ=0.87/0.77/0.65). The 3 raters diagnosed HOD in 38-46% (FLAIR), 40-47% (T2) and 53-67% (PD) of the patients. False positive findings in the control group were less frequent in T2 than in PD and FLAIR (2.2%/8.9%/6.7%). In 53% of the patients the intensity difference between both IONs on PD was significantly increased in comparison to the control group. These patients also showed significantly decreased FA and increased MD. Conclusion: While the rater-based approach yielded the best performance on T2 imaging, a quantitative, more sensitive HOD diagnosis based on ION intensities in PD and DTI imaging seems possible.